2007
DOI: 10.1194/jlr.m600301-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipoprotein lipase and statins on cholesterol uptake into heart and skeletal muscle

Abstract: Regulation of cholesterol metabolism in cultured cells and in the liver is dependent on actions of the LDL receptor. However, nonhepatic tissues have multiple pathways of cholesterol uptake. One possible pathway is mediated by LPL, an enzyme that primarily hydrolyzes plasma triglyceride into fatty acids. In this study, LDL uptake and tissue cholesterol levels in heart and skeletal muscle of wildtype and transgenic mice with alterations in LPL expression were assessed. Overexpression of a myocyte-anchored form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…It has also been found that skeletal muscle LDL‐C uptake is increased in statin‐treated mice overexpressing lipoprotein lipase (LPL) in skeletal muscle (Yokoyama et al. 2007). These data suggest that LPL [the primary enzyme for intravascular hydrolysis of triglyceride (TG)], could also be an important mediator of skeletal muscle cholesterol uptake.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that skeletal muscle LDL‐C uptake is increased in statin‐treated mice overexpressing lipoprotein lipase (LPL) in skeletal muscle (Yokoyama et al. 2007). These data suggest that LPL [the primary enzyme for intravascular hydrolysis of triglyceride (TG)], could also be an important mediator of skeletal muscle cholesterol uptake.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that skeletal muscle LDL-C uptake is increased in statin-treated mice overexpressing LPL in skeletal muscle. 47 These data suggest that LPL (the primary enzyme for intravascular hydrolysis of triglyceride [TG]), could also be an important mediator of skeletal muscle cholesterol uptake by increasing the availability of LDLC from VLDL/IDL conversion. Notably, statins increase LPL serum mass and activity in T2D.…”
Section: Challenges Opportunities and Lessons From Statin Therapymentioning
confidence: 99%
“…10,14 In rat cardiomyocytes, HMGCR activity has been suggested to account for the intracellular cholesterol levels, 18,19 although cardiomyocytes may acquire cholesterol from the circulation. 20 Recent metabolites profile studies using mass spectrometry-based analysis combined with high-temperature gas chromatography show an 7-fold increase in cholesterol levels in hypertrophic cardiac tissues. 21 However, in our studies, mice fed chow supplemented with ≤1.5% cholesterol for 15 days did not exhibit significant differences in the magnitude of cardiac hypertrophy induced by Ang II (unpublished observations).…”
Section: Srebp Pathway Inflammationmentioning
confidence: 99%